Religious diversity a philosophical assessment - Basinger, David (Ashgate philosophy of religion series, 2002)
Religious diversity exists whenever seemingly sincere, knowledgeable individuals hold incompatible beliefs on the same religious issue. Basinger's survey of the relevant literature, proposed solutions, and fresh insights offer an invaluable contribution not only for philosophers of religion and philosophical theologians but for anyone interested in the increasingly significant question of what a religious believer can or cannot justifiably say about their religious perspective.